2007
DOI: 10.1158/0008-5472.can-07-2544
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of let-7a-3 in Epithelial Ovarian Cancer Is Associated with Low Insulin-like Growth Factor-II Expression and Favorable Prognosis

Abstract: MicroRNAs (miRNA) are endogenous noncoding small RNAs that regulate the activity of mRNAs. Many miRNA genes, including let-7a-3, are located in CpG islands, suggesting possible epigenetic regulation of their expression. Promoter CpG island methylation of tumor suppressor genes is involved in cancer development and progression. Using real-time methylation-specific PCR and real-time reverse transcription-PCR, we analyzed DNA methylation in the let7a-3 gene and miRNA expression of let-7a in 214 patients with epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
176
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(189 citation statements)
references
References 20 publications
6
176
2
2
Order By: Relevance
“…Under certain conditions, miRNAs can switch from their repression to activation function through upregulating their targets (Vasudevan et al, 2007), such as let-7a. Lu et al (2007Lu et al ( , 2011 found that ectopic let-7a expression significantly activated the expression of insulin-like growth factor (IGF)-II, which was reported to play an important role in the tumor progression of ES (Zhan et al, 1995), and some clinical trials that target IGF/IGF-1R/Akt axis are under investigation for future ES treatments (Huang et al, 2011). Thus, these conflicting reports promote us to explore the exact function and relative molecular mechanisms of let-7a in ES.…”
mentioning
confidence: 99%
“…Under certain conditions, miRNAs can switch from their repression to activation function through upregulating their targets (Vasudevan et al, 2007), such as let-7a. Lu et al (2007Lu et al ( , 2011 found that ectopic let-7a expression significantly activated the expression of insulin-like growth factor (IGF)-II, which was reported to play an important role in the tumor progression of ES (Zhan et al, 1995), and some clinical trials that target IGF/IGF-1R/Akt axis are under investigation for future ES treatments (Huang et al, 2011). Thus, these conflicting reports promote us to explore the exact function and relative molecular mechanisms of let-7a in ES.…”
mentioning
confidence: 99%
“…We performed a systematic literature and database search in NCBI and found 11 miRNAs (miR-373, miR-520c, miR-126, miR-335, miR-10b, let-7a-1, let-7a-2, let-7a-3, miR27a, miR-21, miR-145) to be involved in breast cancer with known mechanisms [30][31][32][33][34][35][36][37]. In order to identify potential new SNPs as well as to verify the annotated SNPs from the NCBI SNP database in these segments, we sequenced these 10 pre-miRNA genes in a sample set of more than 100 randomly chosen familial breast cancer cases.…”
Section: Resultsmentioning
confidence: 99%
“…All the 11 miRNAs have been reported to be associated with breast cancer initiation, progression, and metastasis and with known mechanisms [30][31][32][33][34][35][36][37]. We systematically scanned for SNPs located in these breast cancer-relevant miRNA genes (including pre-miRNAs and about ±200 bp flanking regions) by sequencing these regions, and then investigated the four most promising SNPs which were selected according to the defined criteria in a large German familial study cohort.…”
Section: Introductionmentioning
confidence: 99%
“…64 Recent research suggests that DNA methylation may also be involved in the regulation of microRNA expression in ovarian cancer, and the methylation can be reversed by DNA methyltransferase inhibitors. 9,65 Indeed, microRNA control and deregulation may be more complex as widespread microRNA repression by transcription factors such as c-myc (that targets miR-195/miR-497) have also been found to contribute to tumourigenesis. 66 Our data demonstrate decreased p53 expression in primary peritoneal carcinoma relative to ovarian serous carcinoma.…”
Section: Discussionmentioning
confidence: 99%